Using Bourdieu to understand the function of digital literacy in an English class: A case study of a higher education university in Namibia - Eiseb, Juliet M (School of Education, 2017)
First year students at a Higher Education University in Windhoek in a Principles of Language English class are expected to use Information and Communication Technologies (ICTs) to improve their language proficiency in a fun and interesting manner. However, it was observed that students have varied digital literacy skills which are not in line with Namibia's ICT Policy. The study set out to find out why students who came from the same Namibian secondary public schooling system, and was exposed to the same curriculum, had such varied digital literacy proficiency. Principal of Language is the natural environment for the researcher and the students in this study. This study follows Eshet-Alkalai's definition of digital literacy. Bourdieu's concept of cultural capital was used to develop an explanation for the observed varied digital literacy skills and to find out if English lecturers should continue with the use of ICTs in the English class. This study was limited to the specific needs and digital literacy deficiency of students as observed in the Principal of Language class. Data was collected from 47 first time Principles of Language, first year students. In addition, this study also relied on the experiences of two ICT subject lecturers. Different data collection instruments were used: student questionnaires, interviews and focus group discussions and faculty interviews. The study revealed that despite Namibia's ICT policy that calls for learners to be prepared at high school for the integration of ICTs, quite a number of first year students had no digital literacy skills. Some students only got to use a computer for the first time at university. Despite these challenges students were not averse to the use of ICTs to improve their English but expect lecturers to first teach them how to use the tools. Lecturers need to realise that not all first year students are computer literate.